The teaching-learning process of the continuity of real variable functions: A literature review - Maxil-Cardoso, G. Elizabeth; Castro-Fernández, Felipe; Juárez-Lopez, José Antonio (Mahesa Research Center, 2024)
This article´s objective is to present the current state of research on the teaching-learning process of continuity of real variable functions. To achieve this, a documentary research design with a qualitative approach and a descriptive depth level was adopted. The instruments for data collection and analysis included a search log, a bibliographic matrix, and a synthesis matrix, created using Excel software. The technique used for the literature review was qualitative content analysis, based on deductive analytical categories: objective, theoretical framework, research method, and conclusions. Advanced searches were conducted on Google Scholar, on Scopus and Web of Science and out of the total results found, 13 relevant articles published during the period 2020-2023 were selected. Among the main findings, the use of a variety of theoretical frameworks in the foundation of the analysed studies was identified, such as the theory of semiotic representations, the MTSK model, the TPACK, and the conceptual contributions of Tall and Vinner, among others. Additionally, a growing interest in the use of technological tools, such as GeoGebra, to enhance the teaching and learning process of mathematics in general, and the continuity functions in particular. Although its limitations, it was identified that this software can be used as a tool for visualization, construction, representation and communication of mathematical knowledge.